2003
DOI: 10.1126/science.1081331
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Shadowing of Primate Sequences to Find Functional Regions of the Human Genome

Abstract: Materials and Methods 1. Generation of sequencing targets. Sequencing targets were amplified from genomic DNA using Platinum Taq HiFi (Invitrogen) following the manufacturer's recommendations, with primers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
410
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 458 publications
(415 citation statements)
references
References 13 publications
4
410
0
1
Order By: Relevance
“…Boffelli et al (25) have shown recently that phylogenetic shadowing of primate sequences that includes sequence from as few as four to six primates in addition to humans is sufficient for the identification of functional elements in the human genome, many of which are likely to be missed by human-mouse comparisons. Consistent with these observations, our previous analysis of TNF-␣ sequences in the primate lineage demonstrated that such an approach is a powerful tool for the identification of candidate regions important for gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Boffelli et al (25) have shown recently that phylogenetic shadowing of primate sequences that includes sequence from as few as four to six primates in addition to humans is sufficient for the identification of functional elements in the human genome, many of which are likely to be missed by human-mouse comparisons. Consistent with these observations, our previous analysis of TNF-␣ sequences in the primate lineage demonstrated that such an approach is a powerful tool for the identification of candidate regions important for gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This has been accomplished through comparison of the human genome with the genomes of a wide-range of species from primates to fish [1][2][3][4]. The underlying success of this strategy is based on comparing sufficiently divergent genomes to distinguish neutral versus functionally constrained sequence elements [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…LD analysis generally identifies more than 30,000 of candidate genes for a specific pathology and evidences the major risk alleles [139]. Although this analysis is very suggestive and likely gives a clear identification of potential candidate genes for a single pathology, as suggested for instance in cancer [21], it still in infancy because of the presence of many genes with modest effects [17]. Thus, many efforts are actually in progress in order to separate ''robust'' genes from ''modest'' genes.…”
Section: Zinc-hsp70 Gene Interactionmentioning
confidence: 98%